Targeting Valuable Chemical Commodities: Hydrazine‐mediated Diels‐Alder Aromatization of Biobased Furfurals - Cioc, Răzvan C.; Crockatt, Marc; Waal, Jan C.; Bruijnincx, Pieter C. A. (ChemSusChem, 2022)
A hydrazine‐mediated approach towards renewable aromatics production via Diels‐Alder aromatization of readily available, biobased furfurals was explored as alterative to the more classical approaches that rely on reactive but uneconomical reduced dienes (e. g., 2,5‐dimethylfuran). To enable cycloaddition chemistry with these otherwise unreactive formyl furans, substrate activation by N,N‐dimethyl hydrazone formation was investigated. The choice of the reaction partner was key to the success of the transformation, and in this respect acrylic acid showed the most promising results in the synthesis of aromatics. This strategy allowed for selectivities up to 60 % for a complex transformation consisting of Diels‐Alder cycloaddition, oxabridge opening, decarboxylation, and dehydration. Exploration of the furfural scope yielded generic structure‐reactivity‐stability relationships. The proposed methodology enabled the redox‐efficient, operationally simple, and mild synthesis of renewable (p‐disubstituted) aromatics of commercial importance under remarkably mild conditions. (Redox) detour? Not for furfural hydrazones! Derivatization as N,N‐dimethyl hydrazone enables the use of furfurals in the production of renewable oxygenated aromatics via a redox‐neutral Diels‐Alder‐based route. In combination with acrylic acid as dienophile, a tandem cycloaddition/decarboxylation/dehydration takes places in remarkably mild conditions en route towards valuable aromatic aldehydes.